Compliance, efficacy and quality of life for oral morphine versus transdermal fentanyl patch in management of cancer pain - N., Gauridas Singha; Deka, Arun; Dakua, Dipankar (International Journal of Research in Medical Sciences, 2022)
Background: A randomized, open, two-period, crossover study was done on cancer patients requiring strong opioid analgesia (n=104, mean age 63.5, range18-83 years) recruited from State Cancer Institute, Gauhati Medical College and Hospital, comparing transdermal fentanyl with oral morphine. Methods: Patients received one treatment for 15 days followed immediately by the other for 15 days. Results: Transdermal fentanyl provided good pain relief and it was also was associated with less constipation when compared to oral morphine(p<0.05). Of those who were able to express a preference, significantly more preferred fentanyl patches. Conclusions: Transdermal fentanyl patch provided good pain relief, equivalent to that provided by oral morphine, required lesser rescue doses, improved quality of life and is associated with less constipation when compared to morphine, and was preferred more by patients.